Rose, hawthorn and pear datas to Hont historical county - Kerényi-Nagy, Viktor; Bakay, László; Bőhm, Éva Irén (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
In this article we published some new Rosa, Crataegus and Pyrus datas from Čebovce: Kő-hegy (Central Slovakia). The most important findings were Crataegus ovalis Kit. (7th locality in Slovakia, cf. Baranec, 1986), Rosa bohemica H. Braun (1st locality in the county) and Pyrus × amphigenea Domin ex Dostalek. The research was supported by „VEGA 1/0246/13 Stratégie využitia vody xerofytnými drevinami a bylinami v urbanizovanom prostredí a krajine” project.